2016
DOI: 10.1515/botcro-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of the Bulgarian endemic Betonica bulgarica Degen et Neič. (Lamiaceae) from Sinite Kamani Natural Park, Eastern Balkan Range

Abstract: Four populations of Betonica bulgarica Degen et Neič. at Sinite Kamani Natural Park were morphologically tested. Intrapopulation and interpopulation variabilities were established. The rеlationship between morphological variability, number, area and ecological appurtenance of the studied populations were explored. The results demonstrated that the main source of phenotype variation is intrapopulation variability, mainly due to the age structure of populations. The most variable traits are height of stem and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The present results in accordance with Cantino (1990) finding. The results showed also, three types of stomatal development within the studied species; diacytic, anisocytic and pericytic and this result agree with EL-Gazzar & Watson (1970), Inamdar & Bhatt, (1972) and Grozeva et al (2016). While Metcalfe & Chalk (1979), stated that, diacytic stoma type was the most common in Lamiaceae.…”
Section: Lamina (Table 5; Plate 6)supporting
confidence: 87%
“…The present results in accordance with Cantino (1990) finding. The results showed also, three types of stomatal development within the studied species; diacytic, anisocytic and pericytic and this result agree with EL-Gazzar & Watson (1970), Inamdar & Bhatt, (1972) and Grozeva et al (2016). While Metcalfe & Chalk (1979), stated that, diacytic stoma type was the most common in Lamiaceae.…”
Section: Lamina (Table 5; Plate 6)supporting
confidence: 87%
“…In recent years, the Bulgarian populations of B. bulgarica have been studied by Grozeva et al [12][13][14]. Along with morphological, palinomorphological, and ecological studies, the authors also draw attention to the epidermis covering the leaves, stems, and flower parts of the plants as the main structure responsible for the accumulation of essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…Betonica species have been used for centuries in folk medicine to treat certain tumors, inflammatory diseases, high blood pressure, ulcers, cough, menopausal problems and as a sedative [11,20,21]. Betonica bulgarica, an endemic species that shows significant similarities with the medicinal plant Betonica officinalis, has been well characterized in regard to phytochemical and morphoanatomical traits [2][3][4]. Chemical analyses have revealed that Betonica bulgarica extracts and essential oils are a rich source of flavonoids and sesquiterpenes with beneficial effects for human health [3,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…It grows on carbonate, grey and brown forest soils in the Central and Eastern Balkan range and in the Thracian plain [1,2]. There is a significant amount of information about the general ecological, anatomical and morphological features (including palinomorphological traits) of this endemic species growing in Bulgaria [3,4]. Analyses of chemical composition, mineral and flavonoid content of several Betonica bulgarica populations have been reported [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation